2021
DOI: 10.1145/3452378
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Physically Consistent Trajectories

Abstract: Trajectories are usually collected with physical sensors, which are prone to errors and cause outliers in the data. We aim to identify such outliers via the physical properties of the tracked entity, that is, we consider its physical possibility to visit combinations of measurements. We describe optimal algorithms to compute maximum subsequences of measurements that are consistent with (simplified) physics models. Our results are output-sensitive with respect to the number k of outliers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In this study, the result of matching for each point of a Noise is typically present in the raw movement data collected by tracking devices. In this study, the raw trajectories including noises (outliers) are identified based on the average speed of moving objects and eliminated from the dataset [22,23]. The moving object travels a certain distance based on an average speed recorded by GPS receivers based on a constant sampling rate (e.g., 15 s).…”
Section: Map Matchingmentioning
confidence: 99%
“…In this study, the result of matching for each point of a Noise is typically present in the raw movement data collected by tracking devices. In this study, the raw trajectories including noises (outliers) are identified based on the average speed of moving objects and eliminated from the dataset [22,23]. The moving object travels a certain distance based on an average speed recorded by GPS receivers based on a constant sampling rate (e.g., 15 s).…”
Section: Map Matchingmentioning
confidence: 99%
“…In Custers et al (2021), a new method category based on physical movement properties is introduced, such as speed (Optimal Speed-bounded) and acceleration (Optimal Acceleration-bounded). This method defines limits on the minimum and maximum allowed values for these properties and uses them to determine whether a point in the trajectory is consistent with the model.…”
Section: Heuristic-based Techniquesmentioning
confidence: 99%
“…No trabalho [Duarte and Sakr 2023], é apresentado um método para gerar ground-truth, ou seja, um método para gerar um conjunto de targets ou labels que posteriormente podem ser usados para treinar e testar um ou mais modelos, utilizando validac ¸ão cruzada. Especificamente, esse método serve para gerar labels de 'outliers' ou 'ruído' em quatro conjuntos de dados distintos, que serão utilizados para avaliar os métodos de detecc ¸ão de outliers, e limpeza de trajetória, implementados em sete bibliotecas: (i)Movetk [Custers et al 2021]; (ii) Moving Pandas [Graser and Dragaschnig 2020]; (iii) Scikit-mobility [Pappalardo et al 2022]; (iv) Ptrail [Haidri et al 2021]; (v) Pymove [Sanches 2019, Bráz 2020]; (vi) Argosfilter [Freitas and Freitas 2022]; (vii) Stmove [Seidel et al 2019].…”
Section: Outlier Detection and Cleaning In Trajectories: A Benchmark ...unclassified
“…Outra forma de identificar pontos de parada é através da verificac ¸ão da consistência da trajetória sobre um modelo físico [Custers et al 2021]. Neste trabalho uma versão deste algoritmo foi implementada usando como modelo físico um limite mínimo de velocidade.…”
Section: Maximum Physically Consistent Trajectoriesunclassified
See 1 more Smart Citation